The effects of porcine somatotropin (pST) and dietary lysine level on growth performance and carcass characteristics of finishing swine - R C Thaler; B R Schricker; G E Fitzner; A J Lewis; Robert D Goodband; Jim L Nelssen; Robert H Hines; Donald H Kropf (Kansas Agricultural Experiment Station Research Reports, 1988)
Seventy-two finishing pigs averaging 130 lb were utilized to determine the effects of PST and dietary lysine on growth performance and carcass characteristics. Pigs were injected daily with 4 mg PST in the extensor muscle of the neck and fed either a pelleted corn-sesame meal diet (.6% lysine, 17.7% crude protein) or diets containing .8, 1.0, 1.2, or 1.4% lysine provided by L-lysine HCl. All diets were formulated to contain at least 200% of NRC (1979) recommendations for other amino acids. Control pigs received a placebo injection and the .6% lysine diet. Increasing levels of dietary lysine resulted in increased average daily gain (ADG) and improved feed conversion (F/G; linear and quadratic, P<.01) for PST-treated pigs. Adjusted backfat thickness (ABF) was not affected by dietary lysine; however, PST-treated pigs had less backfat (P<.05) than control pigs. Longissimus muscle area (LMA), trimmed ham, and loin weights increased as dietary lysine was increased among PST-treated pigs (linear and quadratic, P<.01). Percentage of moisture and crude protein of the longissimus muscle increased, (linear P<.05, linear and quadratic P<.05, respectively), whereas dry matter and fat content decreased (linear P<.05). Similar trends in composition were observed for other ham muscles (semimembranous, semitendinosus, and biceps femoris). Heart, liver, kidney, spleen, and lung weights were not affected by PST or lysine treatment. Urea concentrations in plasma on day 28 decreased linearly (P<.O I) as lysine level increased, whereas plasma lysine and insulin increased (linear and quadratic, P<.OI). Plasma glucose and free fatty acid concentrations on day 28 tended to increase (quadratic P<. I0) with increasing dietary lysine level. Plasma somatotropin level was elevated 2 to 3 times in PST-treated pigs compared to control pigs, but was not affected by dietary lysine level. Our results indicate a relatively high requirement for lysine in PST-treated pigs. Growth performance and carcass traits were optimized at dietary lysine levels of 1.2 to 1.4%, which corresponds to lysine intakes of 30 to 36 g/day. These results demonstrate that PST-administration nearly doubles the lysine requirement of finishing swine.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Porcine somatotropin; Lysine; Growth; Carcass composition